The Antibacterial Activity Of Several Sponges From The Waters Of Tasik Ria Against Escherichia coli And Staphylococcus aureus bacteria - Abrianto A. O. Rompis; Fitje Losung; Deiske A. Sumilat; Agung B. Windarto; Stenly Wullur; Laurentius T. X. Lalamentik (Sam Ratulangi University, 2019)
The sponge is one of the sea organisms that has a prospect as a source of natural compounds including peptides, steroids, asetogenin, terpenoids, alkaloids, cyclic halide and nitrogen. This research was directed to obtain several species of sponges from the waters of Tasik Ria as well as testing the antibacterial activity of extracts from some of the sponge against the bacteria Escherichia coli and Staphylococcus aureus. From the identification, seven species of sponges were found, which consists of: Amphimedon sp., Axinosa sp., Aaptos sp., Theonella sp., Cribochalina sp., Hyrtios sp., and Lendenfeldia sp. The tests of antibacterial activity of the extracts from these sponges against test bacteria E. coli and S. aureus showed some positive results. Extract from Axinosa sp. sponge(16 mm) showed the strongest antibacterial activity on Escherichia coli bacteria. Followed by Hyrtios sp. extract (13.5 mm), Aaptos sp. extract (13 mm), Lendenfeldia sp. extract (13 mm) and Cribochalinai sp. extract(10.5 mm). While the the tests on Staphylococcus aureus bacteria showed that the strongest antibacterial activity was found from Axinosa sp. sponge extract (16.5 mm), followed by the extract from Aaptos sp. (15 mm), Lendenfeldia sp. extract (14.5 mm), Hyrtios sp. extract(13.5 mm) and Cribochalina sp. extract (11 mm).Keywords: Sponge, antibacterial, Escherichia coli, Staphylococcus aureus ABSTRAK Spons merupakan salah satu biota laut yang sangat prospektif sebagai sumber senyawa bahan-bahan alami antara lain peptide, terpenoid, steroid, asetogenin, alkaloid, halide siklik dan senyawa nitrogen. Penelitian ini diarahkan untuk mendapatkan beberapa spesies spons dari perairan Tasik Ria serta menguji aktivitas antibakteri dari beberapa ekstrak spons terhadap bakteri Escherichia coli dan bakteri Staphylococcus aureus. Hasil identifikasi spons ditemukan sebanyak tujuh spesies yang terdiri dari: Amphimedon sp., Axinosa sp., Aaptos sp., Theonella sp., Hyrtios sp., Cribochalina sp. dan Lendenfeldia sp.. Aktivitas antibakteri dari beberapa ekstrak spons terhadap bakteri uji E. coli dan S. aureus terdapat diameter zona hambat bervariasi yaitu bakteri Escherichia coli menunjukkan aktivitas antibakteri ekstrak spons terkuat pada spons Axinosa sp (16 mm), disusul ekstrak spons Hyrtios sp. (13,5 mm), ekstrak spons Aaptos sp. (13 mm), ekstrak spons Lendenfeldia sp. (13 mm) dan ekstrak spons Cribochalinai sp. (10,5 mm). Sedangkan pada bakteri Staphylococcus aureus menunjukkan aktivitas antibakteri ekstrak spons terkuat yaitu: ekstrak spons Axinosa sp. (16,5 mm), disusul ekstrak spons Aaptos sp. (15 mm), ekstrak spons Lendenfeldia sp. (14,5 mm), ekstrak spons Hyrtios sp. (13,5 mm) dan ekstrak spons Cribochalina sp.(11mm).Kata Kunci : Spons, Antibakteri, Escherichia coli, Staphylococcus aureus